Religious tolerance in Southeast Asia: issues and challenges - Wahyono, Zubaidi; Gamon, Alizaman Dumangcag; Akbar Shah @ U Tun Aung, Maulana (IIUM Press, 2024)
In the contemporary global landscape, religious tolerance has emerged as a critical issue across both Muslim-majority and non-Muslim countries. Shared concerns, such as freedom of religion, conversion, freedom of worship and propagation, and violence stemming from religious misunderstandings—including extremism and terrorism—have garnered significant global attention. Addressing these issues is vital for fostering peaceful coexistence and understanding among diverse religious communities. The objective of the study is to understand the concept of tolerance and how it is applied in Southeast Asian countries, particularly in the national policies of Malaysia, Indonesia, Myanmar, and the Philippines. These policies provide public space for religious tolerance, thereby opening the door for the protection of freedom of religion and addressing other religious issues currently taking place in the region. Given the socio-political and religious dynamics in the region, this study aims to investigate the underlying causes of conflicts, insurgencies, terrorism, and religious tensions. By identifying these root causes, the research seeks to contribute to a deeper understanding of the complex factors driving instability and violence in the area. This study offers a thorough analysis of various perspectives on religious tolerance within the ASEAN region, framed through the lens of multiculturalism. By integrating contemporary literature with detailed field observations, the study aims to provide a nuanced understanding of how religious tolerance is reflected and practiced in the constitutions, national laws, and policies of the member countries. The study reveals that instances of intolerance, extremism, conflict, and violence observed across the region are predominantly influenced by economic, social, and political factors, rather than being primarily motivated by religious concerns. In summary, the study argues that attributing conflict, violence, and extremism to the teachings of a religion—which typically promotes love, peace, and mutual respect—misconstrues the root causes. The findings suggest that economic and social inequalities, ethnicism, and political policies are more significant factors contributing to the national instability experienced across the region.